Do Beavers Improve the Habitat Quality for Magellanic Woodpeckers? [¿Los Castores Mejoran la Calidad del Hábitat Para el Pájaro Carpintero Magallánico?] - Vergara-Egert, P; Soto-Gonzalez, G (2012)
The effect of the disturbances caused by the American beaver (Castor canadensis), introduced to the Cape Horn Biosphere Reserve, on species of birds that are forest habitat specialists is poorly understood. Using telemetry data, we determined which attributes of abandoned beaver meadows have a strong impact on habitat selection by the Magellanic woodpecker (Campephilus magellanicus). We detected a positive relationship between the woodpecker habitat use and the fraction of old-growth forest located near these meadows. These results suggest that favorable habitat conditions are generated around small meadows with old-growth forest, because they might increase availability of wood-boring larvae.
Keywords: American beaver; Campephilus; habitat selection